Governing Business Systems Theories and Challenges for Systems Thinking in Practice (Springer Proceedings in Business and Economics,, 2018)
Based on papers from the 4th Business Systems Laboratory International Symposium (BSLAB) in 2016, this volume contributes to the business management, organizational and innovation literature by providing insights on the antecedents of systems thinking in the business systems domain. The Business Systems Laboratory International Symposium addresses current global economic and social challenges from a systemic perspective, drawing from the domains of management, economics, engineering and sociology. In particular, the 2016 Symposium focuses on the epistemological, theoretical, methodological, technical and practical contributions that represent advancements in the theory and practice of governing business systems to address present and future challenges in the global economy. The contributions explore the application of systems thinking to governance, involving the introduction of new administrative organizational and managerial activities aimed toward organizational innovation and control.